1997
DOI: 10.1084/jem.185.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Location in the Cryptococcus neoformans Capsule Is a Determinant of Antibody Efficacy

Abstract: Monoclonal antibodies (mAbs) to the polysaccharide capsule of Cryptococcus neoformans can prolong survival in mice. However, the properties of antibodies that mediate protection are not fully understood. The IgM mAbs 12A1 and 13F1 originated from the same B cell and differ only by somatic mutations in their variable regions; yet mAb 12A1 protects against serotype D infection, while mAb 13F1 does not. Phage peptide display libraries were used to analyze the fine specificity of these two mAbs. The selection of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 35 publications
2
112
0
Order By: Relevance
“…Both mAbs activate the classical complement pathway, but mAb 12A1 suppresses capsular activation of the alternative complement pathway (16). The differences in immunofluorescence-binding pattern, capsular reaction, competition studies, and peptide mimotope reactivity indicate that these two mAbs bind to different epitopes in GXM (12,13,17).…”
Section: Ryptococcus Neoformans Is the Only Pathogenic Fungusmentioning
confidence: 99%
See 2 more Smart Citations
“…Both mAbs activate the classical complement pathway, but mAb 12A1 suppresses capsular activation of the alternative complement pathway (16). The differences in immunofluorescence-binding pattern, capsular reaction, competition studies, and peptide mimotope reactivity indicate that these two mAbs bind to different epitopes in GXM (12,13,17).…”
Section: Ryptococcus Neoformans Is the Only Pathogenic Fungusmentioning
confidence: 99%
“…These two IgMs originated from the same B cell, use the same V region, but differ in certain complementaritydetermining region amino acid sequences as a result of somatic mutations, which in turn result in differences in specificity (12). mAbs 12A1 and 13F1 both protect against infection with serotype A isolates, but only mAb 12A1 protects against serotype D infection (13). mAbs 12A1 and 13F1 produce annular and punctate fluorescence patterns with serotype D isolates, respectively (14).…”
Section: Ryptococcus Neoformans Is the Only Pathogenic Fungusmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, only some epitopes elicited a protective response in mice infected with C. neoformans [23]. Moreover, the protective response was also dependent of the gamma sub-isotype of murine antibodies used in passive transfer experiments [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mouse background also shown to influence the protection given by IgG subclass antibodies [68] thus underscoring the complex relationship between the cellular and humoral components of the immune system. Further studies from the same group revealed that epitope specificity of the MAbs is the critical factor that determines the serotype-specific protection rendered by the anti-C. neoformans MAbs and to confer protection against distinct serotypes of C. neoformans [69].…”
Section: Demonstration Of Protective Role Of Antibodies In Fungal Infmentioning
confidence: 99%